Teacher’s Roles in Technology-Mediated TBLT in EFL Class - Amara, Jihan; Saefullah, Hilmansyah (Innovative: Journal Of Social Science Research, 2025)
This study investigates the role of teachers in Technology-Mediated Task-Based Language Teaching (TBLT) in the context of English as a Foreign Language (EFL) at a vocational high school. Using a qualitative case study approach, data were collected through classroom observations and teacher interviews. The findings highlight the role of teachers in three stages of TBLT: Pre task, Task Cycle, and Language Focus. In the Pre-task stage, teachers act as motivators and presenters, activating students' background knowledge using PowerPoint and guiding initial understanding. During the Task Cycle, teachers facilitate group collaboration and monitor students' progress while using smartphones to explore tenses. In the Language Focus stage, teachers provide feedback and use Baamboozle as a technological tool for formative assessment. The study demonstrates that teachers' roles extend beyond pedagogy to include digital integration, which aligns with the principles of TMTBLT. These findings provide insights into how technology and task-based methods can enhance language teaching in school settings and promote student centered learning.